Assessment of Postoperative Follow-up for Patients with Recurrent Kidney Stone - Kadhim, Haleema; Jaddoue, Betool; Al-Shamma, ihsan (Iraqi National Journal of Nursing Specialties, 2005)
Abstract Kidney stones are one of the most common and most painful medical problems known (1). Nurses assess and monitor patients through diagnosis and treatment and teach patients how to avoid recurrence of stones (2). A descriptive study was conducted on 150 patients diagnosed with recurrent kidney stones, who were attending the out patients consultation urology disease clinics at surgical specialties, Al-Kadhimia, Al-Yarmook, and Al-Karama Teaching Hospital and Extracorporeal shock wave lithotripsy (ESWL) departments for the period from the 1st of Feb. 2002 through to the end of May 2004. The aim of the study is to assess the post-operative follow-up for patients with recurrent kidney stones. None- probability (purposive sample) of 150 patients with recurrent kidney stones The reliability and validity of the instrument were determined through a pilot study. The data were collected through the use of constructed questionnaire and analysis through the application of descriptive statistical analysis procedures which included. (Frequency, percentage, mean score, stander deviation, relative sufficiency) and application of inferential statistical analysis which included the (Chi-square)